Indonesian Marriage Legal System Construction In Order to Protect Children From Marriage Law That is Not Recorded - . Amnawaty (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The legal system of marriage in Indonesia there are three kinds. First Indigenous legal the system, theSecond the system of Islamic law, the three Western legal the system. Indigenous legal systems ofmarriage can still be found in the country of Indonesia both ritual of "consent granted" in the sense oflegitimacy and ritual ceremonies that accompany the validity of the marriage procession still found many.the Second the Islamic legal system, the system is still alive in the community that the majority ofLampung population is Muslim. Third Western legal system applicable as positive law means the law inforce at this time in the land of Indonesia. Results reveal that the construction of Customary Law, IslamicLaw and Western Law all three protects the children born of the marriage unregistered. It's just thedifference between Islamic law and Customary Law with Western Law is Islamic law and Customary lawrun by the community and not become positive law, so if there are problems in the implementation ofIndigenous law and Islamic law, the positive law are powerless to solve it. Thus arises the various effectssuch as smuggling law, impunity, etc.. Marriage Act as part of the Law of the West in terms of the writtenlaw does not protect the children born of the marriage that is not recorded